Augustine's correspondence with Pascentius (epp. 238-241): an epistolary power game? - Löhr, Winrich Alfried (Revue d'études augustiniennes et patristiques, 2016)
The article analyzes the correspondence between Augustine and the comes domus regiae Pascentius (Augustin, epp. 238-241): First one attempts to determine the date, occasion and circumstances of these letters. Then a detailed analysis of the letters is offered which places them in context: The correspondence continues in written form the power game of the preceding disputation between Augustine and Pascentius. Our analysis shows the dynamic of the correspondence, the diverging self-definitions, aims, tactics and rhetorical tools used by the opponents. For Augustine both disputation and correspondence aim at correcting the doctrinal error of Pascentius and making him publicly and in written form confess his error. It is very difficult for Pascentius to thwart the aggressive and deliberate approach of the bishop of Hippo.
Keywords: Augustinus, Aurelius <Heiliger> / Pascentio Augustinus